A New Differential Protection Scheme for Rotor Windings of Type 3 Wind Generator (DFIG) Depends on Park Transform - حجار عمار; حسن عزت; خليل هبا (Latakia University Journal -Engineering Sciences Series, 2022)
In the last years, the investment of wind energy has increased for electric power production as a clean and sustainable source, under a large increase in demand for energy by consumers. The Doubly-Fed Induction Generator (DFIG) is one of the most widely used types of wind generators in modern wind farms, due to the ability to control of rotation speed in proportion of wind speed and control both the real and reactive power independently. The rotor of these generators is exposed to many faults due to the nature of its design. These faults may load to damage the generator and trip of wind plant and consequently to great economic losses. Accordingly, the interest in protecting wind generators from faults has increased recently. Therefore, this paper presents a new differential protection scheme to protect the rotor of wind generator from faults. This scheme depends on using the Park Transformation in order to obtain and compare the differential currents in d – q frame. This scheme takes into account the dynamic variations of the rotor frequency which has extremely low values during different operations modes. To verify the performance of the adopted differential protection scheme in this paper, a wind plant with a type 3 wind generator DFIG was modeled in MATLAB/SIMULINK software environment and several internal and external faults of rotor was simulated. The results of modeling and simulation proved the effectiveness and reliability of the adopted protection scheme to protect the rotor windings of the wind generator from all faults, as well as its ability to distinguish between internal and external faults.